Heterovalent Cation Substitutional and Interstitial Doping in Semiconductor Sensitizers for Quantum Dot Cosensitized Solar Cell - Ningning Zhang; Xiaoping Zou; Yanyan Gao (International Journal of Photoenergy)
Doped films of TiO2/PbS/CdS have been prepared by successive ionic layer adsorption and reaction (SILAR) method. Bi- and Ag-doped-PbS quantum dot (QD) were produced by admixing Bi3+ or Ag+ during deposition and the existing forms of the doping element in PbS QD were analyzed. The results show that Bi3+ entered the cube space of PbS as donor yielding interstitial doping Bi-doped-PbS QD, while Ag+ replaced Pb2+ of PbS as acceptor yielding substitutional doping Ag-doped-PbS QD. The novel Bi-doped-PbS/CdS and Ag-doped-PbS/CdS quantum dot cosensitized solar cell (QDCSC) were fabricated and power conversion efficiency (PCE) of 2.4% and 2.2% was achieved, respectively, under full sun illumination.